Analisis Mentoring, Kompetensi dan Manajemen Keperawatan Terhadap Penerapan Model Praktik Keperawatan Profesional - Dardin, Dardin; Rian Adi, Pamungkas; Hasyim, Ahmad (Poltekkes Kemenkes Mataram, 2025)
Efforts to improve the quality of nursing care and work effectiveness of nurses in hospitals are influenced by the availability of competent nurses, the application of nursing management and mentoring which can increase the application of the nursing profession practice models (NPPM) in the wards. The purpose of this study was to determine the application of NPPM in hospitals. Research design usingcross sectional with analytical quantitative research methods using linear regression test with path analysis with 119 respondents. The results of this study are basedThree Box Method obtained the value and category of nursing management variables of 98.74, mentoring of 94.6 and the application of NPPM of 88.10 including the high category while the variable competence of nurses is 83.56 in the medium category. The results of the analysis showed a relationship between mentoring of 0.573 and nurse competence of 0.534 for nursing management while nursing management of 0.455 for the application of NPPM. The results of the multiple correlation test of mentoring and nurse competence obtained R=0.677 and R Square =0.458 while the results of the regression test of mentoring and nurse competency on nursing management obtained R=0.677 with a significance value of 0.000. The results of the double correlation test of mentoring and nurse competence on the application of NPPM through nursing management obtained a value of R = 0.532 and R Square = 0.283 with the equation of the regression line being Y = 19.076 + 0.223 mentoring + 0.218 nurse competence + 0.226 nursing management with a significance value of 0.000. The application of NPPM in the ward can be maximized with a management approach, nurse competence, professional relations, nursing care system, and reward compensation system in accordance with nursing standards by implementing mentoring, increasing competence, implementing management in the ward